Home Cooking Trends Coming out of Early Covid-19 Period - Menaka, S. (Proceedings of Peradeniya University International Research Sessions 2021, Sri Lanka, Vol. 23, 11th & 12th November 2021, 2021)
The worldwide pandemic Covid-19 has had an impact on Sri Lanka as well. The lockdown implemented due to the harmful disease has affected routine life, jobs, education and travel plans of the people. Individuals began to prefer home prepared meals rather than purchasing food from outside. The purpose of the study was to explore the trend of home cooking in the Jaffna district due to the first wave of Covid-19 (March-April 2020). Local people were requested to fill out a questionnaire which contained questions related to cooking and food practices. Interviews were carried out with food corner employees. Bulk buying and storing of groceries before lockdowns were seen among the participants. Working women responded that home cooking gave an opportunity to enhance family bonding as members of the family actively engage in cooking. According to the survey, people used garlic, ginger, turmeric and asafoetida in their dishes, which they believed was effective to fight against the infection. 18% of the respondents did not purchase perishable foods externally due to the fear of spreading of virus. Instead, they used homegrown food ingredients for home cooking. Food safety measures such as washing fruits and vegetables with salt water, avoiding buying food from outside and not sharing food were practiced. People hesitated to buy food from outside due to considerations related to disease transmission. Movement restriction shifted their food practices towards home cooking. The trend of take away food from local food corners declined as people carry home-cooked lunch to work to optimize hygiene. Work from home and online learning caused a dramatic shift in food practices where home cooking was found to be the best choice with the limited groceries available during the pandemic. Despite many hardships experienced due to the pandemic, one positive outcome is people have discovered the joy of home cooking along with healthy food handling practices.
Keywords: Covid 19; Pandemic; Home cooking; Meal pattern; Food safety